Rekonstruksi Epistemologi Tauhid dalam Pemikiran Ismail Raji Al-Faruqi: Basis Integrasi Agama dan Sains di Era Globalisasi - Rahmi Maldini Efendi; Eva Dewi; Arini Rahman (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2025)
This article examines the reconstruction of tawḥīd epistemology in the thought of Ismail Raji al-Faruqi as a foundation for the integration of religion and science in the era of globalization. The study departs from the epistemological problem within the modern Muslim world, namely the dichotomy between religious sciences and secular sciences resulting from the dominance of secular paradigms in the modern system of knowledge. Consequently, the development of science has often been detached from ethical and spiritual dimensions. This research employs a philosophy of science approach through library research using a critical-conceptual analysis of the works of Ismail Raji al-Faruqi and relevant literature on the Islamization of knowledge and the integration of religion and science. The findings reveal that al-Faruqi’s tawḥīd epistemology is constructed upon interconnected ontological, epistemological, and axiological dimensions. This framework emphasizes five principles of unity: the unity of God, creation, truth and knowledge, life, and humanity, which function as an integrative foundation linking revelation and reason, religion and science, as well as morality and the development of modern knowledge. Furthermore, al-Faruqi formulates the Islamization of knowledge as a project of epistemic de-secularization through twelve systematic steps aimed at reconstructing the paradigm of modern science based on the Islamic worldview. A critical dialogue with Syed Muhammad Naquib al-Attas, Ziauddin Sardar, and Osman Bakar demonstrates that al-Faruqi’s thought possesses particular strengths in its institutional and methodological dimensions, although it still requires enrichment in metaphysical, ethical, and postcolonial critiques of modern knowledge hegemony. This article concludes that tawḥīd epistemology offers an integrative, humanistic, and transcendental alternative paradigm for addressing the crisis of secularized knowledge and remains relevant as a philosophical foundation for the development of Islamic education and science in the contemporary global era.